A Phase III study of oral steroid administration versus local steroid injection therapy for the prevention of esophageal stricture after endoscopic submucosal dissection (JCOG1217, Steroid EESD P3). (5th August 2015) - Mizutani, Tomonori; Tanaka, Masaki; Eba, Junko; Mizusawa, Junki; Fukuda, Haruhiko; Hanaoka, Noboru; Takeuchi, Manabu; Aoyama, Ikuo; Kojima, Takashi; Takizawa, Kohei; Ono, Hiroyuki; Muto, Manabu
Abstract : A randomized Phase III trial commenced in Japan in September 2014. Endoscopic local steroid injection has been commonly used and considered acceptable as the current standard treatment for the prevention of esophageal stricture after endoscopic submucosal dissection for superficial esophageal cancer. The purpose of this study is to confirm the superiority of prophylactic oral steroid administration following endoscopic submucosal dissection in terms of stricture-free survival over endoscopic local steroid injection for patients with superficial esophageal cancer. A total of 360 patients will be accrued from 35 Japanese institutions within 2.5 years. The primary endpoint is stricture-free survival, and the secondary endpoints are the number of endoscopic balloon dilations for 12 weeks after endoscopic submucosal dissection, adverse events, serious adverse events and the proportion of patients with dysphagia score ≤1 at 12 weeks after endoscopic submucosal dissection. This trial has been registered in the UMIN Clinical Trials Registry as UMIN000015064 (http://www.umin.ac.jp/ctr/index.htm ).